2004
DOI: 10.1046/j.1365-2923.2004.01785.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of evidence-based education on a perinatal capacity-building initiative in Macedonia

Abstract: The intervention has increased the capacity of Macedonians to practise best-evidence perinatal medicine and improve outcomes. Sustainability is predicted by the "train the teachers" approach, with concurrent strengthening of the infrastructure and organisational framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 16 publications
0
45
1
Order By: Relevance
“…Ten (22.2%) of the 45 studies reported a breakdown of scores according to cadre, 26,36,39,40,44,50,53,55,56,74 and 7 (70.0%) of these studies showed that birth attendants from lower cadres (eg, midwives) improved significantly more from pretraining to posttraining than those from higher cadres (eg, physicians). 26,40,42,50,53,56,74 In all 7 of these studies, significant differences in pretraining test performance between different cadres were diminished or completely eliminated upon retesting after training. Similarly, a study from HBB in Tanzania found that nurses outperformed health care providers of both higher and lower training levels on a standardized OSCE.…”
Section: Association Between Birth Attendant Characteristics and Acqumentioning
confidence: 87%
See 3 more Smart Citations
“…Ten (22.2%) of the 45 studies reported a breakdown of scores according to cadre, 26,36,39,40,44,50,53,55,56,74 and 7 (70.0%) of these studies showed that birth attendants from lower cadres (eg, midwives) improved significantly more from pretraining to posttraining than those from higher cadres (eg, physicians). 26,40,42,50,53,56,74 In all 7 of these studies, significant differences in pretraining test performance between different cadres were diminished or completely eliminated upon retesting after training. Similarly, a study from HBB in Tanzania found that nurses outperformed health care providers of both higher and lower training levels on a standardized OSCE.…”
Section: Association Between Birth Attendant Characteristics and Acqumentioning
confidence: 87%
“…36 Nine studies (20%) attempted to correlate performance on either standardized tests or actual behavior in the delivery room with changes in neonatal mortality statistics, and the results were mixed. 18,30,31,37,42,60,62,64,73 Four (44.4%) of these studies documented significant declines in neonatal mortality correlating with improvement in test scores and delivery room behavior, respectively. 30,31,42,60 Five studies (55.6%) reported no improvement in mortality despite improvement in test scores and/or delivery room behavior.…”
Section: Impact Of Theoretical Knowledge On Delivery Room Behaviors Amentioning
confidence: 99%
See 2 more Smart Citations
“…415 Recent data from a perinatal intervention trial in Macedonia indicate that it may be possible to reduce perinatal and neonatal mortality at the national scale through a concerted perinatal education and health worker-training program within the health system setting. 416 Similarly, the introduction of a structured primary care program in Bolivia, 417 coupled with maternal care, led to a dramatic reduction in infant and young child mortality. In 1992-1993, the annual rates of mortality of children Ͻ5 years old were 205.5 per 1000 and 98.5 per 1000 in the comparison and intervention areas, respectively.…”
Section: Promotion Of Smoking Cessation During Pregnancymentioning
confidence: 99%